Micronutrients deficiencies (poor levels of antioxidants Vitamin A and Vitamin C) and Academic Performance of Selected Young Girls in Sokoto, Nigeria - Sarkingobir, Yusuf; Imam, Aminu Umar (ARKA INSTITUTE, 2024)
It is widely stressed that girl-child education is good; and girls could only learn properly if they are fed well. Levels of micronutrients such as antioxidants vitamins A and C could lead to poor brain or nervous system functions. The objective of this work was to evaluate the relationship between Micronutrients deficiencies (poor levels of antioxidants Vitamin A and Vitamin C) and academic performance of selected young girls in Sokoto, Nigeria. This work determined blood levels of vitamin A and C in 250 young girls in Sokoto using standard methods and materials of analytical grade. A semi experimental study involving 40 selected study participants was done. An exploration of academic performance of subjects that are with enough vitamin C and A and their counterparts was done using assessment. This study shows that, the girls with normal levels of antioxidants vitamins A and C scored a mean mark (55.0+ 13.015) more than those with poor levels (35.63+12.63) (p<0.05). This signifies that nutritional concerted interventions are needed. Nutritional education, soil fertilization, bio fortification, and relations could be used for improving public diet in the state.